CONCEPTUAL AUDIT ECOSYSTEM FOR INDONESIA ELECTRONIC-BASED GOVERNMENT SYSTEM - Hari Setiabudi Husni (Asosiasi Dosen Muda Indonesia, 2022)
In the Presidential Regulation of the Republic of Indonesia Number 95 of 2018, the consideration section states that to realize clean, effective, transparent, and accountable governance and quality and reliable public services are required electronic-based government system (EBGS) and to improve the integration and efficiency of electronic-based government system is required governance and management of electronic-based government system nationally. EBGS general design has a variety of infrastructure and application needs to be used by central and local governments. This research was conducted to analyze the terms and needs of an ecosystem of electronic-based government system audits so as to achieve EBGS utilization integration and efficiency nationally. The research looks specifically at the implementation of audit process in the presidential regulation from the point of view of human resources, audit management and audits supporting infrastructure needed by the audit ecosystem to be able to run. The analysis will be conducted, among others, comparing the implementation stages by the government with the ideal design as stated within the literature, conducting interviews and disseminating questionnaires to audit ecosystem stakeholders (policy makers, policy supervisors, implementors activities and audit objects operators), the results of gap analysis between existing conditions and the ideal concept of ecosystem will be examined further to produce suggestions for improvement and development to ensure the formation of audit ecosystem mandated perpres 95/2018 is achieved.